EFEITO DE DIFERENTES PARÂMETROS PRODUTIVOS NO CRESCIMENTO INICIAL DE MUDAS DE Bauhinia variegata LINN - SILVA, Hebert Lizardo Germano da; COUTO, Allan Motta; VIEIRA, Vanessa Aparecida Cassol; FRANCO, Alex Quaresmoa; MENEZES, Rayane Aparecida Silva (ANAIS DO ENIC, 2018)
-